Estimation of power analysis in WLAN infrastructure - Shanmugasundaram, N; N. Ganesh, E; Kumar, N (International Journal of Engineering and Technology, 2018)
Design of indoor WLAN infrastructure requires prediction of radio waves propagation inside the building, which can be a complex problem. Therefore some sort of planning is required before the wireless networking hardware is set up.The goal of this work is to provide an estimate of the received power within a building. Physical environment is a large office building, of which we consider one part. The building is constructed of various materials. In this paper, we present a model that simulates the considered problem. Received power is calculated and compared to receiver minimum input level sensitivity given by the IEEE 802.11 Standards. Numerical results were obtained using MATLAB.Â